Optimising blast pulls and controlling blast-induced excavation damage zone in tunnelling through varied rock classes. (March 2019) - Salum, Amiri Hamis; Murthy, V.M.S.R.
Highlights: Rock characterization methods suggested for blast pull optimization and overbreak reduction. Allowable peak particle velocities during blasting were suggested for minimizing overbreak in different rock classes. Optimum round lengths of excavation for top heading in different rock classes are proposed. Blast pull and sequence of excavation in varied rock classes should be optimized from time cycle and overbreak viewpoints. Method of charging of perimeter holes is also suggested for different round lengths for reduced overbreak. Abstract: Tunnelling is the sole means of providing access for transportation, water conveyance in hydropower, mining of minerals, etc. Hydropower alone contributes to about 19% of the commercial energy needs of India and construction of hydroelectric power projects to meet these needs involves huge amounts of tunnelling through varied rock mass conditions. This necessitates identifying methods of tunnelling that are cost-effective, suited to varied geology and yet rapid to commission the projects in place of continuous excavation systems like TBM and Roadheader which are geology sensitive, costly and completely imported thus constraining their smooth adaptation. Mechanized drilling and advanced blasting techniques are the most often used methods of excavation of tunnels in India and in other countries for rapid and cost effective tunnelling, which depends, to a large extent, on the blast performance. Among the outcomes of any blasting operation, pull or advance achieved per blast and blast-induced excavation damage are of major concerns. It is essential to limit the blast-induced damage so as to control time and cost overruns in an underground project more so in varied geology. This paper discusses determination of optimum round lengths of excavation in varied rock classes as well as controlling overbreak in tunnelling. The sequence of excavation, requirements for both top heading and bench are also addressed. It has been observed from the past experiences that round lengths up to 5 m are practiced in rock class I and as the class improves to VII, the pull attempted reduces to about 1 m. Since charging of perimeter holes contributes to overbreak in underground excavations, a thorough analysis of the design of blasting pattern and scheme of charging for minimizing overbreak has been suggested. Characterization of ground through seismic imaging coupled with ground vibration monitoring has been suggested to control blast – induced rock damage and also arrive at optimum charges. As evident in this paper, characterization of the ground is the most important step towards rapid tunnelling.